Building Collaborative Networks to Support Academic Integrity: Keynote address for Manitoba Academic Integrity Network (MAIN) Academic Integrity Inter-Institutional Meeting 2021 - Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2021)
Academic integrity work can be time-consuming and invisible, but you are not alone. Learn how a systems approach and formal and informal networks provide academic integrity experts and advocates with support to learn with and from one another. By the end of this session engaged participants will: • Understand how the academic integrity community is developing, both in Canada and internationally. • Find out how you can get support and get involved. • Reflect on your how your experience, expertise, and wisdom can help others.